STRUCTURE–ACTIVITY RELATIONSHIPS AND BIOORGANIC ANALYSIS OF CONSTITUENTS FROM PHLOMOIDES LABIOSA - Nozima Holiqova (International Scientific and Current Research Conferences, 2025)
Phlomoides labiosa is an understudied species of the Lamiaceae family known for its potential reservoir of biologically active secondary metabolites. This study investigates the chemical composition of P. labiosa and examines the structure–activity relationships (SAR) of its major constituents through an integrated bioorganic approach. Sequential extraction followed by chromatographic fractionation enabled the isolation of phenolic acids, flavonoids, terpenoids, sterols, and related metabolites. Structural identification was performed using GC–MS, HPLC, FT-IR, UV–Vis, and NMR spectroscopy. Biological activity assays demonstrated significant antioxidant and antimicrobial effects, with phenolic and terpenoid-rich fractions showing the highest functional potency. SAR analysis revealed a strong correlation between hydroxylated aromatic structures and radical-scavenging activity, while terpenoid skeletons were associated with antibacterial efficiency. The results indicate that Phlomoides labiosa contains structurally diverse natural compounds with promising pharmacological potential, supporting further targeted isolation and mechanistic studies for bioactive molecule development.